2012
DOI: 10.1021/am301119b
|View full text |Cite
|
Sign up to set email alerts
|

Improved Electrical Conductivity of Polyamide 12/Graphene Nanocomposites with Maleated Polyethylene-Octene Rubber Prepared by Melt Compounding

Abstract: Electrically conductive polyamide 12 (PA12)/graphene binary nanocomposites with a low percolation threshold of 0.3 vol % were prepared by melt compounding. A rapid increase in electrical conductivity from 2.8 × 10(-14) S/m of PA12 to 6.7 × 10(-2) S/m was achieved with ~1.38 vol % graphene. It is shown that graphene sheets were homogeneously dispersed in PA12 matrix. Furthermore, polyethylene-octene rubber grafted with maleic anhydride (POE-g-MA) was used to further enhance the electrical conductivity of PA12/g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(61 citation statements)
references
References 44 publications
0
55
0
1
Order By: Relevance
“…We found the conductivity to increase with increasing graphene loading level, reaching 3 S/m for the 40 vol% sample. This value is higher than the maximum conductivity observed in most papers describing graphene-filled composites which tend to fall in the range 10 -2 -10 S/m [refs [86][87][88][89][90][91][92][93][94]], although at least one paper described conductivities as high as 300 S/m. [95] In addition, this is considerably higher than the best results reported for most nanotube-filled composites.…”
Section: Electrical Properties Of Fibresmentioning
confidence: 54%
“…We found the conductivity to increase with increasing graphene loading level, reaching 3 S/m for the 40 vol% sample. This value is higher than the maximum conductivity observed in most papers describing graphene-filled composites which tend to fall in the range 10 -2 -10 S/m [refs [86][87][88][89][90][91][92][93][94]], although at least one paper described conductivities as high as 300 S/m. [95] In addition, this is considerably higher than the best results reported for most nanotube-filled composites.…”
Section: Electrical Properties Of Fibresmentioning
confidence: 54%
“…As shown in the curve, the PDMS/SCF composite sheets prepared by the SCFNA process (P2) exhibit a rapid transition from electrically insulating to conducting with a low percolation threshold of 0.15 wt%, implying the formation of a continuous and compact SCF network for electrons transport in the matrix. The addition of bolting cloth further improved the electrical conductivity of the PDMS/SCF composite sheets with a lower percolation threshold of 0.06 wt%, which is much lower than PA12/MWNT nanocomposites prepared by melt compounding (0.9 wt%) reported by Socher et al, 44 and polyamide 12/ graphene nanocomposites with maleated polyethylene-octene rubber (0.65 wt%) reported by Yan et al, 35 The electrical conductivity (s) follows the power law at loadings near the percolation threshold (4 c ).…”
Section: Resultsmentioning
confidence: 72%
“…34,35 With suitable fraction ratio of the two polymers and thermodynamic conditions, a co-continuous two-phase structure with selected location of the llers in one polymer could be obtained, which serves as continuous conductive network. Recently, Yan et al 35 reported improved electrical conductivity of polyamide 12/ graphene nanocomposites with maleated polyethyleneoctene rubber prepared by melt compounding, both higher electrical conductivity and storage modulus were obtained when most graphene sheets were located in PA12 matrix rather than that in POE-g-MA phase. The third method is to form a segregated structure in the composites by compressing a mixture of polymer granules decorated with conductive llers via dry or solution mixing to construct the segregated conductive networks.…”
Section: -16mentioning
confidence: 99%
“…S/m and is indeed observed when the premixed SEG/PP and PE were mixed for 20 min, in sharp contrast to the 4 wt % SEG needed in originally (SEG/PP)/PE procedure. A low percolation at nearby 1 wt % SEG was indeed obtained, which is lower than those of many other graphene-filled systems with same loading of graphene by melt compounding (Kim et al, 2011;Yan et al, 2012), and even comparable to those of some systems prepared by solution-mixing (Yoonessi & Gaier, 2010). When SEG sheets are distributed throughout the PE phase, as opposed to being concentrated at the blends interface, this remarkable reduction in the percolation threshold is never observed upon the increasing mixing times of the blends, and what's more, when the SEG was firstly mixed with less favorable phase PP, the localization of SEG could be optimized located at the interface by processing parameter control.…”
Section: Fine-tuning Of (Seg/pp)/pe Compositesmentioning
confidence: 67%